The Level of Knowledge of Hepatitis B Infection Among Turkish Dental Students (Annals of Medical Research, 2021)
Aim: Dentists are at high risk of hepatitis B infection. The aim of this study was to evaluate the knowledge of students from Ordu univeriyt, faculty of dentistry on hepatitisMaterials and Methods:Questionnaires consisting of 76 questions related to students’ socio-demographic status, knowledge of hepatitis infection about the ways of transmission, prevention and risk groups, and vaccination status were distributed to all dental students.Results: Total of 155 students participated in the study and completed the questionairre. The level of knowledge of the 4th and 5th year students was significantly higher than the other students (p=0.001). Fifth year students had significantly better knowledge about the transmission and prevention ways of the hepatitis when compared with the 1st year students B (p=0.001). Although, only 60% percent of the students have been vaccinated, the vaccination rates were higher in both 4th and 5th year-students when compared to the other classes. Fourty-one percent of the students did not know that HBV is contagious during asymptomatic period.Conclusion: There was a lack of knowledge about the hepatitis B infection especially among the 1st and 2nd year students. Therefore, the continuous education of infectious diseases is required starting from the first year of the dental school.
Keywords: Dental Students; Hepatitis B; Knowledge.